FOLHETIM EM TELA: A estrutura do romance-folhetim na série televisiva Game of Thrones - FIGUEIREDO, Isadora Fernandes da Silva (2022)
This study aims to analyze the recorrence of the structure of the serial novel (feuilleton) in the television series Game of Thrones (2011-2019), by David Benioff and D.B. Weis, based on studies of the Cultural Industry disseminated by the Frankfurt School, mainly by the theorists Max Horkheimer (1944) and Theodor Adorno (1985) and the assumptions of Reception Aesthetic Theory. In this sense, the subject presented here will explore the construction that relates art and industry – with an emphasis on literature, more precisely – at the beginning of the publication of the novel-feuilleton, which took place from the 1830s onwards, in France. The feuilleton was shaped as mass culture, that is, art produced by technique, to bring profit to Industry and entertainment for those who consume it. To provide a better understanding of the structure of this genre and how it influenced other genres, especially television series, authors such as Umberto Eco (1964), Antônio Zuin (2001), Douglas Kellner (2006), György Lukács (2009), Antônio Gramsci (1986), Edgar Morin (1997), Marlyse Meyer (1996), Arlindo Machado (2011), Vincent Colonna (2010), among others. Concerning the television series, the elements of the serial novels present in the television series Game of Thrones were identified. Such elements were noticed mainly through studies related to the Theory of Aesthetics of Reception, postulated in the studies of Hans Robert Jauss (1967) and the Culture of Convergence, identified in the studies of Henry Jenkins (2008), which confirm the importance of reception with regard to the public's teleparticipation in Tv series. Thus, through bibliographical, qualitative, and exploratory research, the preliminary results of this research were achieved. With this, it was possible to understand how there was the transposition of some structures present in the serial novel to the television series as a way to hold the audience's attention, such as the repetition of themes, the redundancy of dialogs, and the public's control over the content exposed.